In vivo quantification of gentamicin released from an implant coating. (July 2016) - Nast, S; Fassbender, M; Bormann, N; Beck, S; Montali, A; Lucke, M; Schmidmaier, G; Wildemann, B
Drug-releasing implants are gaining increasing interest. The present study reports a detailed physicochemical analysis of a polymeric coating based on poly(D, L-lactide) and the incorporated gentamicin combined with an in vitro and in vivo study of the gentamicin release. Differential scanning calorimeter, Fourier transform infrared spectroscopy, gel permeation chromatography and high-performance liquid chromatography showed no effect of the gamma sterilisation on the coating components or an interaction of the polymer and the gentamicin. Microbiological analysis revealed an inhibition of bacterial growth on the implant surface. For the in vivo study, gentamicin-coated wires were implanted into the tibiae of rats and harvested at different time points up to day 42. To monitor the release in vivo, gentamicin was quantified in serum, bone, endosteum, kidney, and on the explanted wires. Gentamicin was detectable over a time period of 42 days in the endosteum, up to seven days in the kidney, up to 4 h in the bone and at the end of the experiment on one of eight wires. The locally released gentamicin caused no histological changes of the kidney. Microbiologically active concentrations of released gentamicin were found in the endosteum up to 4 h after implantation. The combination of different methods supports the individual results, where quantification is complemented by visualisation or antimicrobial activity. This work demonstrates that the coating procedure results in no substantial alteration of the incorporated drug and that the in vitro burst release occurs also in vivo .